Deteksi Boraks pada Bakso di Kota Kupang dengan Menggunakan Kertas Tumerik - Nenoharan, Elzabat Metriani; Malelak, Gemini E. M.; Sulmiyati, Sulmiyati; Sipahelut, Geertruida M. (Animal Agricultura, 2024)
This study aims to find out whether meatballs circulating in Kupang city use borax. The test was carried out using a qualitative test to match the results of borax detection using turmeric paper. Organoleptic test, affirmation test and water binding test. This research was carried out at the Undana Livestock Product Technology Laboratory. The variables observed were borax detection using turmeric paper, organoleptic test, affirmation test, and water binding test. The results showed that from 25 it was 20%. Ampel meatballs taken from traders in Kupang City. The results using turmeric paper showed that there were 5 meatball traders who used borax, organoleptic test results showed that the color and texture were not compared while the aroma and taste there were differences where the borax aroma score was higher (3.06) compared to meatballs that were not detected borax (P<0.05).. Thetaste score detected by borax was higher (3.70) compared to that detected by undetected borax (P<0.05). The results of the affirmation test showed that there was no difference between the detected and undetected meatballs, and the results of the water binding test showed that there was no difference between the detected borax and the undetected borax.From the results of this study, it can be concluded that the results of research on borax content in meatballs in Kupang City there were 5 samples that were positive for borax. The organoleptic test results showed that aroma (3.06) and taste (3.70) (P<0.05). The results of the affirmation test showed no real effect (P<0.05). Water binding test had no noticeable effect (P<0.05)